2004
DOI: 10.1104/pp.104.048116
|View full text |Cite
|
Sign up to set email alerts
|

Combined Transcript and Metabolite Analysis Reveals Genes Involved in Spider Mite Induced Volatile Formation in Cucumber Plants

Abstract: Many plants have an indirect defense against herbivores by emitting volatiles that attract carnivorous enemies of the herbivores. In cucumber (Cucumis sativus) the production of carnivore attractants can be induced by herbivory or jasmonic acid spraying. From the leaves of cucumber plants with and without spider mite infestation, two subtractive cDNA libraries were made that were enriched in cDNA fragments up-or down-regulated by spider mite infestation. A total of 713 randomly selected clones from these libra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
98
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
3
3

Relationship

1
9

Authors

Journals

citations
Cited by 133 publications
(105 citation statements)
references
References 47 publications
4
98
1
Order By: Relevance
“…S5). Several other TPSs producing (E)-b-ocimene or (E,E)-a-farnesene or both of these terpenes have been identified previously from gymnosperms (TPS-d; Martin et al, 2004) and in the TPS-a, -b, -f, and -g subfamilies of angiosperms (Dudareva et al, 2003;Arimura et al, 2004;Mercke et al, 2004;Nieuwenhuizen et al, 2009; Supplemental Fig. S5).…”
Section: Tps02 and Tps03 Expression Is Under Constitutive Control In mentioning
confidence: 99%
“…S5). Several other TPSs producing (E)-b-ocimene or (E,E)-a-farnesene or both of these terpenes have been identified previously from gymnosperms (TPS-d; Martin et al, 2004) and in the TPS-a, -b, -f, and -g subfamilies of angiosperms (Dudareva et al, 2003;Arimura et al, 2004;Mercke et al, 2004;Nieuwenhuizen et al, 2009; Supplemental Fig. S5).…”
Section: Tps02 and Tps03 Expression Is Under Constitutive Control In mentioning
confidence: 99%
“…Paré et al 1999;Bouwmeester et al 1999); (4) blends of HIPV not only emanate from the leaf under attack by the herbivore, but are also systemically induced in the plant (Turlings and Tumlinson 1992;Dicke 1994;Guerrieri et al 1999); (5) application of jasmonic acid (JA), a phytohormone, to wild-type plants or defence-signalling mutants leads to production of volatiles similar to HIPV (Hopke et al 1994;Ozawa et al 2000;Gols et al 2003;Thaler et al 2002;Van Poecke and Dicke 2003;Ament et al 2004); (6) herbivore-induced gene expression patterns in plants are similar to those mediated by jasmonates (e.g. Kant et al 2004;Ament et al 2004;Mercke et al 2004;Reymond et al 2004); (7) elicitors of HIPV synthesis in the plant have been found in the regurgitate/saliva of herbivores [N-(17-hydroxylinolenoyl)-L-glutamine or volicitin: Alborn et al 1997Alborn et al , 2000β-glucosidase: Hopke et al 1994;Mattiacci et al 1995]s.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that upon herbivore attack, plants emit a blend of volatiles, which is composed of more than 200 compounds that are directly responsible for deterring, intoxicating or repelling herbivorous insects (Seybold et al 2006). Alternatively, they can attract the parasitoids and natural predators of offending herbivores, resulting in securing the plant from damage (Mercke et al 2004;Degen et al 2004;Dudareva et al 2013). The transformation of petunia with the (S)-limonene synthase gene from C. breweri results in linalool production that repels aphids (Lücker et al 2001).…”
Section: Genetic Engineering For the Production Of Plant Terpenoidsmentioning
confidence: 99%